2005
DOI: 10.1242/jeb.01871
|View full text |Cite
|
Sign up to set email alerts
|

Ionoregulatory changes in different populations of maturing sockeye salmonOncorhynchus nerkaduring ocean and river migration

Abstract: ATPase activities observed in spawners suggests that the fish may be attempting to compensate for the osmotic perturbation associated with the decline in plasma chloride concentration and osmolality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 28 publications
5
73
0
Order By: Relevance
“…The results of the present study are consistent with previous reports of gill Na + /K + -ATPase isoform switching in salmonid fish in response to salinity change (Richards et al, 2003;Shrimpton et al, 2005;Bystriansky et al, 2006;Bystriansky et al, 2007a;Bystriansky et al, 2007b), and support the idea that the Na + /K + -ATPase 1a and 1b isoforms each have a specific function for fish living in freshwater and marine environments, respectively. However, the precise roles and functions of the various Na + /K + -ATPase isoforms in salmon gills remain to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study are consistent with previous reports of gill Na + /K + -ATPase isoform switching in salmonid fish in response to salinity change (Richards et al, 2003;Shrimpton et al, 2005;Bystriansky et al, 2006;Bystriansky et al, 2007a;Bystriansky et al, 2007b), and support the idea that the Na + /K + -ATPase 1a and 1b isoforms each have a specific function for fish living in freshwater and marine environments, respectively. However, the precise roles and functions of the various Na + /K + -ATPase isoforms in salmon gills remain to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
“…Wild Arctic char migrating into freshwater have been reported to have significantly higher gill Na + /K + -ATPase activity immediately following freshwater entry (Bystriansky et al, 2007a). Shrimpton and colleagues showed that gill Na + /K + -ATPase activity decreased in 3 of 4 stocks of sockeye salmon monitored while still in seawater en route to enter freshwater (Shrimpton et al, 2005). However, gill Na + /K + -ATPase activity in these stocks then increased when fish were sampled at the spawning grounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Carruth and colleagues (Carruth et al 2000) concluded that Bthe presence of elevated plasma cortisol in upstream migrating, landlocked Pacific salmon suggests that stressors previously considered to cause cortisol increases, such as long-distance migration and changes in salinity, may not be primary causes of the hypothalamic-pituitary-interrenal axis activation.^Cor-tisol in individual O. nerka has been demonstrated to already be high in seawater prior to their upstream migration, and has been suggested to play a role in ionoregulation in the gill as they adapt to freshwater (Flores et al 2012). Cortisol is a well-known osmoregulator (Bradford et al 2010;Milla et al 2009;Mommsen et al 1999;Shrimpton et al 2005); regulation of osmolarity is crucial for the survival of migrating salmon, there being a close correlation between the loss of osmoregulation and death (Jeffries et al 2012). This study by Jeffries and colleagues further examined temporal biochemical/endocrine changes in O. nerka over the final 6 weeks of maturation and senescence (in 2008) and demonstrated that dyotic signaling (low 17β-estradiol in females, low testosterone in males) was present in all fish that died, irrespective of the timing of death (at first sampling, second sampling, third sampling, and final sampling (~week 6)).…”
Section: Ratio Of Sex Steroid/gonadotropin As a Measure Of Dyotic Sigmentioning
confidence: 99%
“…This monumental journey exposes them to numerous physiological challenges, including changes in salinity and temperature, sexual maturation, endurance exercise, and the cessation of feeding resulting in prolonged fasting . Understanding the physiological adjustments required for transfer from seawater to freshwater has received much attention to date (Shrimpton et al 2005;Cooperman et al 2010;Flores et al 2011), whereas the metabolic regulation necessary for endurance exercise and fasting are aspects of fish migration that have received comparatively less exploration. The genomic and metabolic alterations required by salmon to travel such great distances and to complete one of the most remarkable energetic feats in the animal world in a fasted state remain elusive.…”
Section: Introductionmentioning
confidence: 99%